THE FIRST RUSSIAN EXPERIENCE OF ADALIMUMAB TREATMENT IN PSORIATIC ARTHRITIS - Elena Yurievna Loginova; T V Korotaeva; N V Klimova; E N Aleksandrova; L N Denisov; Sh F Erdes (Научно-практическая ревматология)
Objective. To evaluated effect of adalimumab treatment on activity of arthritis, enthesitis, psoriasis and functional status in PsA patients (pts). Subjects and methods. 18 pts with active PsA (12 female, 6 male), median age 43,1±10,2 years (yrs) (range 24-56), median duration of psoriasis 16,7±9,6 yrs (range 4-33), median duration of PsA 9,2±6,7 yrs (range 1,5-23) received Adalimumab 40 mg subcutaneously every other week (wk) for 12 wks in open-label study. Evaluations of treatment effects were conducted by the PSARC, ACR 20, 50 and 70, LEI, PASI, BSA, HAQ and CRP at wks 4 and 12. Results. The sings of activity of PsA at baseline were: DAS=4,8 (4,0; 5,45), LEI=4,25 (0,25; 8,05), PASI=10,5 (7,2; 12,1), BSA=1,75 (1; 2), HAQ=1,125 (0,875; 1,5), СRР=27,9 (11,4; 34,6). After 4 wks all parameters significantly improved: DAS=2,85 (2,1; 3,1), LEI=1,86 (0; 3,97), PASI=6,4 (2,8; 8), BSA=0,75 (0,15; 1), HAQ=0,375 (0,125; 0,625), СRP=1,7 (1,4; 3,2) and were maintained after 12 wks: DAS=1,6 (1,3; 2,03), LEI=0,38 (0; 0,89), PASI=1,1 (0,4; 2,2), BSA=0 (0; 0,9), HAQ=0,312 (0; 0,625), СRР=1,75 (0,7; 3,6); p